2004
DOI: 10.1213/01.ane.0000117147.56528.33
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Motor Blocking Potencies of Intrathecal Ropivacaine: Effects of Concentration

Abstract: The minimum local anesthetic dose for motor block with 0.1% ropivacaine is 50% larger than the 1% concentration with a relative efficacy ratio of 1.5. Our findings suggest that more diluted local anesthetic solutions determine less motor block, and this may be considered in ambulant laboring parturients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
0
11
1
1
Order By: Relevance
“…Camorcia et al reported that the ED 50 for motor block of intrathecal ropivacaine was 50% higher in a 0.1% solution [ 23 ], but this trend was not consistent with our present findings. This phenomenon can be explained as follows.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Camorcia et al reported that the ED 50 for motor block of intrathecal ropivacaine was 50% higher in a 0.1% solution [ 23 ], but this trend was not consistent with our present findings. This phenomenon can be explained as follows.…”
Section: Discussioncontrasting
confidence: 97%
“…Some researchers have reported that the concentration of local anesthetic is an important factor determining the maximum sensory level and motor block of spinal anesthesia [ 6 , 7 ]. Camorcia et al [ 8 ] reported that the concentration of local anesthetic affected the ED 50 for motor block in adults. In our previous study, we also found that the concentration of plain bupivacaine influenced the ED 50 in young patients, demonstrating that the ED 50 for motor block of intrathecally administered bupivacaine with 0.75% bupivacaine was higher than that of the lower concentration (0.375% bupivacaine) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Differences in potency appear to be more pronounced when concentrations less than 0.5% are compared. Camorcia et al (20,21) demonstrated that the dose required for motor block is dependent on the concentration of ropivacaine with a 50% increase in dose requirement between 1% and 0.1% ropivacaine (ED50 6.1 vs 9.1 mg). Using 0.25% ropivacaine they (20) described a minimum local anaesthetic concentration (MLAC) of 3.64 for ropivacaine and 2.94 mg for levobupivacaine.…”
Section: Figurementioning
confidence: 99%
“…Although concentration-dependent pharmodynamics could thus be demonstrated for epidural administration, it seemed that this would be impractical for intrathecal drugs. That was until Camorcia et al 21 performed an elegant up-down study where women received ropivacaine as either 1.0% or 0.1% solutions, and the minimum local analgesic doses (MLAD) were estimated. It was found that dosing requirements were increased by 50% with the dilute solution, hence demonstrating the relative importance of concentration for intrathecal efficacy.…”
Section: Dose Concentration and Volumementioning
confidence: 99%